Prevalence of Cytomegalovirus Infection Among Fertile Women From Yukpa Amerindians Commu nities, State of Zulia, Venezuela - Anais Suárez; F. Monsalve Castillo; Tania Romero; Luciana Costa León; R. Mindiola; María Eugenia Castellano (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Infection by Cytomegalovirus (CMV) is considered a health problem in fertile women when the infection is acquired during pregnancy. In order to find the prevalence of CMV among fertile women in Yukpa communities,112 women out of 151, ages 16 - 45, were selected during 2007, coming from Tokuko (n=41), Kasmera (n=35), Yasa (n=20) and Neremu (n=16). IgG and IgM antibodies for CMV were determined by enzymatic immunoassay technique (EIA). The presence of CMV antibodies was detected in 72, 3% (81/112) of the population studied. The 8,6% (7/81) of those reactive for IgG were positive for anti-CMV IgM. A significant difference (p<0,001) in CMV prevalence was detected in the Tokuko community compared to the Yasa community. Factors such as age, overcrowding, number of partner, number of children and abortions, were not association with the presence of CMV an ti bodies. CMV prevalence in this population is below that indicated for fertile women in other countries and is distributed homogeneously among the communities studied. The percentage of susceptible women must be taken into account through controls before and during pregnancy.